Effects of interventions on physical activity behavior change in children and adolescents based on a trans-theoretical model: a systematic review - Chao Xie; Ziyun Zhang; Xinlu Zhang; Yan Li; Peng Shi; Shuai Wang (BMC Public Health)
Abstract Background The Trans-theoretical Model (TTM) has been applied in numerous empirical studies concerning physical activity (PA) interventions for children and adolescents. Consequently, the aim of this review is to identify and synthesize the evidence regarding the effectiveness of TTM-based interventions in promoting PA behavior change among this demographic, with the goal of informing future research and policy development. Methods A systematic review was performed followed the PRISMA guideline, protocol was registered in PROSPERO (CRD42023416216). Computer-based searches were conducted in the CNKI, Wan-Fang, VIP, Web of Science (WOS), PubMed, and EBSCO databases to identify relevant literature. Two researchers independently conducted the literature screening and quality assessment. The quality of the randomized controlled trials (RCTs) was evaluated using the Risk of Bias Assessment Tool version 5.1.0, as recommended by the Cochrane Collaboration Network. For quality assessment of quasi experiments (QEs), the Risk Of Bias In Non-randomised Studies-of Interventions (ROBINS-I) tool was employed. Results A total of 22 articles were included in the systematic review. Stage-matched interventions and interventions designed based on a more complete structure of the TTM are more likely to promote an increase in the actual levels of PA among children and adolescents, as well as to facilitate an increase in their PA stages. Interventions that combine health information and health behavior feedback are more likely to promote an increase in actual PA levels and the advancement of PA stages; while interventions that include PA programs are more likely to facilitate improvements in health indicators. Conclusion The effectiveness of TTM-based PA behavior change interventions for children and adolescents depends on the specific measures employed. Interventions that are stage-matched and integrate multiple behavior change techniques using the complete TTM structure are more likely to enhance PA and its associated health benefits. However, there are several normative issues that remain. These include the misuse of incremental stages as a substitute for PA, neglect of stage specificity when applying the model, a lack of framework for behavior change techniques in targeted interventions, and an absence of a dynamic feedback process.